Spectroscopy of Cu- and Ag-doped single crystal and glassy lithium tetraborate: luminescence, optical absorption and ESR study - Ignatovych, M.; Holovey, V; Vidoczy, T.; Baranyai, P.; Kelemen, A.; Laguta, V.; Chuiko, O. (Functional Materials, 2005)
Photoluminescence (PL), optical absorption (ОА) and ESR spectra have been studied to characterize Cu- and Ag-doped single crystal and glassy Li₂B₄О₇ (LTB). The attribution of LTB:Cu glass PL as one arising from the sets of Cu⁺ ions with slightly different local environments is proposed. The ОА spectra of Cu-doped single crystal and glass are different in the UV and VIS ranges. The ОА and PL features of LTB:Ag single crystal and glassy are different from each other.